Batik: Souvenirs with Local Wisdom in Tourism Destinations - Oktawirani, Panca; Maziyah, Siti; Nafis, Warda Ayu Berliana (Journal of Gastro Tourism, 2025)
Batik is one of Indonesia's iconic cultural heritages with great potential as a leading product in the creative economy sector and a typical souvenir of tourist destinations. However, the batik industry faces various challenges, such as low labor costs, lack of design and production technology innovation, and minimal utilization of business intelligence to support exports to global markets. This study aims to identify opportunities and challenges in developing batik as a competitive tourist destination souvenir in the international market. Using the methods of data collection and consolidation, information needs analysis, and strategy development, this research proposes a framework for mapping batik potential. Government support through regulations and marketing strategies for batik as a craft art includes market penetration, market development, product development, and diversification. A strategic approach that integrates innovation, sustainability, and community empowerment is expected to expand batik's role as a cultural symbol as well as a significant export commodity.